Attitudinal and behavioral response to coo cues for low involvement product - Chan, Angelina Wan Sian; Muhammad Khalique, Muhd Sadique; Ernest Cyril, de Run (International Journal of Research Studies in Management, 2010)
A considerable number of empirical studies on country-of-origin had indicated its influence on consumer product evaluation as well as purchase intention. Previous research also suggests the outcomes of country-of-origin effect differ by product type investigated in addition to countries selected for examination. The main crux of this study to explore the role that country-of-origin cue plays on Malaysian consumer’s product evaluation as well as purchase intention of a low involvement product i.e. toothpaste. This study considered both local (Malaysia – Colgate) and foreign (China – Darlie and Australia – Sensodyne) brands of toothpaste that were initially determined through a pre-test. Data was collected via a survey utilizing self-administered questionnaires by respondents aged 20 and above and analyzed using means, analysis of variance (ANOVA) as well as T-test. Findings revealed that Malaysians generally prefer products from developed nations as opposed to those made locally or imported from less developed countries. Additionally, it was also found that consumers tend to prefer local toothpaste when compared to the toothpaste made in China. Implications for management are discussed. This study is preliminary in nature and it will be a milestone for the potential contributors.